EFEKTIFITAS MEDIA BLOCK DIENES UNTUK MENINGKATKAN KEMAMPUAN PENJUMLAHAN DERET KE BAWAH BAGI ANAK BERKESULITAN BELAJAR - Isti Oktarandi (Universitas Negeri Padang, 2014)
Abstrak: This research was conducted based on the problem indicating that the students with learning disabilities still needed concrete objects to learn and understand basic Mathematics especially on summing rows downward topic. The similar problem was also found in class V of SD Negeri 17 Jawa Gadut Padang. Therefore, the researcher tried to use block dienes media to improve the students’ basic mathematics ability. The formulation of the research problem was “does the use of dienes block media could improve summing rows downward ability of the student with learning disabilities?”.This was a quantitative research which used experimental method and Single Subject Research (SSR) form with A-B-A design. The subject of the research was a student with learning disabilities in class V of SD Negeri 17 Jawa Gadut Padang. The data was collected through observation and a written test. To see the result achieved by the student clearly, the data gotten was analyzed by using percentage technique. Based on the result of data analysis, it was revealed that the average score in the baseline session (A-1) was 10%, in the intervention session was 76,15% and in the baseline (A-2) was 92%. The tendency of tract in the intervention phase (B) improved. The data overlapped in the baseline condition (A1) to the intervention condition (B), and in the intervention (B) to the baseline 2 (A-2) was 0%. Based on these results, it was concluded that the use of block dienes media could improve summing rows downward ability of the student with learning disabilities.The results of this research were expected to be taken into account by the teachers in using learning media for the students with learning disabilities in Math. Keywords; Media of Dienes Block, summing rows down.